The study of thermal processes during grinding knives from hard-to-cut steels - T.N. Ivanova; G.V. Kozlov; A.Yu. Muyzemnek (Известия высших учебных заведений. Поволжский регион:Технические науки, 2023)
Background. In modern mechanical engineering, knives made of hard-to-cut steels are widely used, the main advantage of which is increased heat resistance and wear resistance. The knives are subject to high demands on the geometric accuracy of surfaces and the physical and mechanical state of the surface layer, which makes it difficult to assign the parameters of their machining. The purpose of the research is to develope mathematical models and to study thermal processes in the grinding of knives from hard-to-cut steels. Materials and methods. Analytical methods for studying thermal processes in plates, mathematical models for the distribution of temperature fields over the surface and depth of the part are used. The results are verified experimentally by metallographic pilot studies. Results. Mathematical models have been developed and computer simulation of thermal processes for typical grinding schemes has been carried out - processing the entire surface line by line for the entire width of the circle, processing along the edge and sharpening the edge of the knife. The results have been verified experimentally by metallographic pilot studies. Conclusions. The effect of temperature in the grinding zone and residual stresses on the surface layer of the workpiece affects the geometric shape of the knives. Warping is the greater, the higher the grinding temperature and the greater the depth of the heated layer on the surface to be ground.